Leaving the revolutionary movement a study of ten cases of former revolutionaries in Panay (1980 to the present). - Gequinana, Bea F.
There have been studies and publications about revolutionary movement and life histories of participants who joined and left the movement. This research paper was then conducted to identify ten participants from Panay Island, describe their processes and present their reason in joining and leaving the revolutionary movement and their current views on the movement. To gather the needed data, library research and internet archiving and personal interviews were done to answer the objectives of the study. The study showed that participants joined the revolutionary movement because of the following reasons: the orientation of the movement, the economic and political conditions prior to their joining and their personal choices. The participants underwent processes which include the movement?s orientation, studies, educational discussions, and pledge to the Party and concern over their decisions particularly the considering their family?s reaction, their safety and sacrifices. While in the movement, these participants have specific tasks assigned to them. They also have various experiences with the enemies, the people and leaders and members of the movement. In leaving the revolutionary movement, their reasons were personal, organizational or both. They also have varied processes in leaving the movement; some became rebel returnees through applying for amnesty and others simply lie low from the movement. Moreover, some participants viewed the revolutionary movement positively and others viewed it negatively.